Comparative analysis of mineralocorticoid receptor antagonists and renin-angiotensin system inhibitors/angiotensin receptor neprilysin inhibitor in heart failure with mildly reduced ejection fraction - Lee, Chia-Chen; Te-Wei Kuan, David; Chang, Kai-Chun; Chen, Zheng-Wei; Cheng, Jen-Fang; Lin, Ting-Tse; Lin, Lian-Yu; Wu, Cho-Kai (Frontiers in Pharmacology, 2024)
Introduction To clarify the efficacy of mineralocorticoid receptor antagonists (MRA) and renin-angiotensin system inhibitors/angiotensin receptor neprilysin inhibitors (RASI/ARNI) in heart failure with mildly reduced ejection fraction (HFmrEF). Methods This study assessed the association between these medications and outcomes in HFmrEF using data from the National Taiwan University Hospital-integrated Medical Database. The primary outcome was cardiovascular mortality/heart failure hospitalization (HHF). Inverse probability of treatment weighting balanced baseline patient characteristics. The exposure of primary interest was use of MRA and use of RASI/ARNI, while the non-user group was also likely to receive other heart failure medication treatment. Results Among 2,584 HFmrEF patients, 17% received MRA and 43% received RASI/ARNI. Predictors of MRA use included older age, slightly higher ejection fraction, and lower NT-proBNP level. RASI/ARNI use was predicted by higher BMI, lower NT-proBNP level, normal uric acid and potassium levels. MRA use was not associated with a lower risk of cardiovascular death [hazard ratio = 0.89, 95% confidence interval (CI): 0.78–1.02] or HHF (hazard ratio = 1.01, 95% CI: 0.94–1.09). Conversely, RASI//ARNI use was linked to a lower risk of cardiovascular death (hazard ratio = 0.82, 95% CI: 0.71–0.94) but not HHF (hazard ratio = 0.995, 95% CI: 0.924–1.07). Landmark analysis showed no significant difference in outcomes for follow-up durations exceeding 2 years. Conclusion MRA had a neutral effect on cardiovascular death and HHF, while RASI/ARNI was associated with a lower risk of cardiovascular death. RASI/ARNI may be more beneficial than MRA for HFmrEF patients. Regular re-evaluation is essential to adjust heart failure treatment.